Solution Processing and Resist‐Free Nanoimprint Fabrication of Thin Film Chalcogenide Glass Devices: Inorganic–Organic Hybrid Photonic Integration. Issue 8 (22nd May 2014) - Zou, Yi; Moreel, Loise; Lin, Hongtao; Zhou, Jie; Li, Lan; Danto, Sylvain; Musgraves, J. David; Koontz, Erick; Richardson, Kathleen; Dobson, Kevin D.; Birkmire, Robert; Hu, Juejun
<x xml:space="preserve">Abstract</x> Organic polymer materials are widely credited with extreme versatility for thin film device processing. However, they generally lack the high refractive indices of inorganic semiconductors essential for tight optical confinement in planar integrated photonic circuits. Inorganic–organic hybrid photonic systems overcome these limits by combining both types of materials, although such hybrid integration remains challenging given the vastly different properties of the two types of materials. In this paper, a new approach is used to realize inorganic–organic hybrid photonics using chalcogenide glass (ChG) materials. Known as an amorphous semiconductor, the glass possesses high refractive indices, and can be prepared in a thin film form through solution deposition and patterned via direct thermal nanoimprinting, processing methods traditionally exclusive to polymer materials only. Sub‐micrometer waveguides, microring resonators, and diffraction gratings fabricated from solution processed (SP) ChG films can be monolithically integrated with organic polymer substrates to create mechanically flexible, high‐index‐contrast photonic devices. The resonators exhibit a high quality factor (Q‐factor) of 80 000 near 1550 nm wavelength. Free‐standing, flexible ChG gratings whose diffraction properties can be readily tailored by conformal integration on nonplanar surfaces are also demonstrated.